Why are the Pakistani maternal, fetal and newborn outcomes so poor compared to other low and middle-income countries? - Aleha Aziz; Sarah Saleem; Tracy L. Nolen; Nousheen Akber Pradhan; Elizabeth M. McClure; Saleem Jessani; Ana L. Garces; Patricia L. Hibberd; Janet L. Moore; Shivaprasad S. Goudar; Sangappa M. Dhaded; Fabian Esamai; et al. (BMC, 2020)
Abstract Background Pakistan has among the poorest pregnancy outcomes worldwide, significantly worse than many other low-resource countries. The reasons for these differences are not clear. In this study, we compared pregnancy outcomes in Pakistan to other low-resource countries and explored factors that might help explain these differences. Methods The Global Network (GN) Maternal Newborn Health Registry (MNHR) is a prospective, population-based observational study that includes all pregnant women and their pregnancy outcomes in defined geographic communities in six low-middle income countries (India, Pakistan, Democratic Republic of Congo, Guatemala, Kenya, Zambia). Study staff enroll women in early pregnancy and follow-up soon after delivery and at 42 days to ascertain delivery, neonatal, and maternal outcomes. We analyzed the maternal mortality ratios (MMR), neonatal mortality rates (NMR), stillbirth rates, and potential explanatory factors from 2010 to 2018 across the GN sites. Results From 2010 to 2018, there were 91,076 births in Pakistan and 456,276 births in the other GN sites combined. The MMR in Pakistan was 319 per 100,000 live births compared to an average of 124 in the other sites, while the Pakistan NMR was 49.4 per 1,000 live births compared to 20.4 in the other sites. The stillbirth rate in Pakistan was 53.5 per 1000 births compared to 23.2 for the other sites. Preterm birth and low birthweight rates were also substantially higher than the other sites combined. Within weight ranges, the Pakistani site generally had significantly higher rates of stillbirth and neonatal mortality than the other sites combined, with differences increasing as birthweights increased. By nearly every measure, medical care for pregnant women and their newborns in the Pakistan sites was worse than at the other sites combined. Conclusion The Pakistani pregnancy outcomes are much worse than those in the other GN sites. Reasons for these poorer outcomes likely include that the Pakistani sites' reproductive-aged women are largely poorly educated, undernourished, anemic, and deliver a high percentage of preterm and low-birthweight babies in settings of often inadequate maternal and newborn care. By addressing the issues highlighted in this paper there appears to be substantial room for improvements in Pakistan's pregnancy outcomes.